تقدير الطلب على الكهرباء في محافظة البصرة للمدة 1995-2010 - خلود موسى عمران; ساهرة حسين الثعلبي (مجلة الغري للعلوم الاقتصادية والادارية)
المستلخص: تتناول الد ا رسة واقع الطاقة الكهربائیة في محافظة البصرة، بوصفها من أهم مصادر الطاقة الرئیسة للبشریة التي تسهم مساهمة كبیرة في شتى القطاعات التي تدفع بعملیة التنمیة الى التقدم، وتعد الطاقة الكهربائیة أحدى السلع الضروریة لمختلف النشاطات والفعالیات، إذ لا یمكن الاستغناء عنها لما لها من أهمیة كبیرة في حیاة مختلف المجتمعات. فالطلب على الطاقة الكهربائیة یت ا زید مع ازدیاد السكان وتحسین الدخول، وتنوع استخدامات الكهرباء والاستی ا رد المفتوح من السلع الكهربائیة من مختلف المناشيء. وتعد كثرة الانقطاع في التیار الكهربائي مشكلة تؤثر سلباً على أغلب النشاطات الیومیة للأف ا رد. لذا أصبح من الضروري د ا رسة العوامل المؤثرة في الطلب على الكهرباء في محافظة البصرة للقطاعین المنزلي والصناعي، خاصة ان الكهرباء طاقة غیر متجددة ویلزم توفرها لجمیع المستهلكین. وقد تم استخدام بعض الأسالیب الإحصائیة في تحلیل الطلب على استهلاك الكهرباء كنموذج وقد أبدى القطاع المنزلي معنویة للاختبا ا رت SPSS التعدیل الجزئي اعتماداً على البرنامج الإحصائي الإحصائیة، إما القطاع الصناعي فقد كان غیر معنوي في جمیع صیغ نموذج التعدیل الجزئي (الخطیة واللوغاریتمیة المزدوجة، والنصف اللوغاریتمیة) إلا انه أبدى معنویة في نموذج الانحدار الخطي البسیط نصف اللوغاریتمي. Abstract: Study addresses the reality of electric power in the province of Basra, as the most important energy sources key to humanity which contribute substantially to the various sectors that drive the development process to progress, and energy is electric one essential goods for various activities and events, can not be dispensed with because of their great importance in the life of the various communities. The demand for electric power is growing with the increasing population and improved incomes, and the diversity of the uses of electricity and open import electrical goods from different origins. The frequent interruptions in the power supply problem affecting negatively on most daily activities of individuals. So it became necessary to study factors affecting the demand for electricity in the province of Basra to the domestic and industrial sectors, especially non-renewable electricity energy needs to be provided to all consumers. I have been using some statistical methods in the analysis of the demand for electricity consumption model partial adjustment depending on the statistical program SPSS has shown the domestic sector morale of statistical tests, either the industrial sector was not significant in all formats model partial adjustment (linear and logarithmic double, and half logarithmic) However, the expressed moral in simple linear regression model semi-logarithmic.